KEEFEKTIFAN LEMBAR KEGIATAN SISWA BERBASIS PENDEKATAN SAINTIFIK PADA MATERI GETARAN DAN GELOMBANG DITINJAU DARI AKTIVITAS DAN HASIL TES KETERAMPILAN PROSES SAINS SISWA KELAS VIII - An Nuril Maulida Fauziah; Tutut Nurita; Deviana Eka Ratna Saftri (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
This research aims to describe the effectiveness of worksheet based on a scientific approach on the vibration and wave materials based on activity and science process skill test. This research uses Pre-Experimental design form with One Group Pretest Posttest Design research design. The subjects of this research are students of 8th grade SMP Al-Falah Deltasari Sidoarjo 2016/2017 school year totaling 26 students. Data collection in this research using the method of observation and test, using student activity sheet instrument and science process skill test sheets. The result of research for student activity has percentage of 85,10%. Classic completeness can be achieved with the percentage of 80.77% and students can improve the science process skills with n-Gain score of 0.80 which belongs to high category.Keywords : effectiveness, scientific approach, science process skill